Fasakh Nikah is Talak Khulu ' in the Perceptive of Muqaranah Mazahib Fil Al-Fiqh and Maqashid Syari'ah - Nurhadi Nurhadi (INSTITUT AGAMA ISLAM NEGERI PALANGKA RAYA, 2020)
ABSTRACTFasakh nikah or khulu' is the husband's divorce right which is given to his wife to break away from the marriage bond which is considered to have no benefit. This study is a study of muqaranah mazahib fil al-fiqh. Khulu 'according to the school of Daud al-Zhahiri, Ibnu Hazm represented, argues that the khulu' is the king's divorce (talak that can be reconciled). According to the Hanbali School represented by Ibn Qudamah that khulu‘ is the fasakh of marriage. Strengthened by Imam Ahmad with the argument of the authentic hadith of Ibn Abbas, as well as the opinion of the Shafi'iyyah school. The maqasid syari'ah review of khulu' in marriage with the maqasid Ammah and Khassah approach, then analyzed using circular theory by understanding the meaning of khulu' based on general benefit, then khulu 'is the wife's divorce, because talak can basically arise from the husband referred to as the rights of divorce and also from the wife referred to as divorce divorce or khulu' or fasakh. Then the wisdom of khulu’ is the solution to the incomplete household that is not resolved, so that the wife is not neglected, the law allows the wife of the talak or divorces the husband with the concept of khulu’ or fasakh in the religious court (sharia court), in return for divorce rights for the wife.Keywords: Fasakh Nikah, Talak Khulu' and Maqashid Syari'ahINTISARIFasakh nikah atau khulu' adalah hak perceraian suami yang diberikan kepada istrinya untuk melepaskan diri dari ikatan pernikahan yang dianggap tidak memiliki manfaat. Penelitian ini adalah penelitian muqaranah mazahib fil al-fiqh. Khulu' menurut mazhab Daud al-Zhahiri, Ibnu Hazm mewakili, berpendapat bahwa khulu' adalah perceraian (talak yang dapat direkonsiliasi). Menurut mazhab Hanbali diwakili oleh Ibn Qudamah bahwa khulu‘ adalah fasakh pernikahan. Diperkuat oleh Imam Ahmad dengan argumen hadis shahih Ibnu Abbas, serta pendapat mazhab Syafi'iyyah. Maqasid syari'ah mengulas khulu' dalam pernikahan dengan maqasid Ammah dan Khassah, kemudian dianalisis menggunakan teori sirkular dengan memahami makna khulu' berdasarkan manfaat umum, maka khulu' adalah perceraian istri, karena talak pada dasarnya dapat timbul dari suami sebagai hak perceraian dan juga dari istri disebut perceraian atau khulu' atau fasakh. Maka khulu' merupakan solusi untuk permasalahan rumah tangga yang tidak dapat diselesaikan, sehingga hak istri tidak diabaikan, hukum memperbolehkan istri menceraikan suami dengan konsep khulu' atau fasakh di pengadilan agama, sebagai imbalan atas hak perceraian untuk istri.Kata Kunci: Fasakh Nikah, Talak Khulu’ dan Maqashid Syariah